Development and effectiveness of a mobile-based autonomy support program for the prevention of metabolic syndrome in middle-aged women - Seo, Miseon; Jun, Eun-Young; Oh, Hyunjin (Frontiers in Public Health, 2024)
Objective Utilizing self-directed strategies for maintaining and managing healthy lifestyle habits is efficient, and it is essential to consider individual motivation, as it is a factor that directly influences the adoption and maintenance of healthy behaviors. The study aimed to assess the effects of a mobile-based autonomy support program on basic psychological needs, autonomous motivation, health behavior, and metabolic syndrome indicators in middle-aged women. Methods This study was a non-randomized controlled trial with a pre-test and post-test design, focused on validating a mobile-based autonomy-supportive program to prevent metabolic syndrome in middle-aged women. The experimental group participated in a 12-week mobile-based autonomy support program, which included components such as education, physical activity guidance, dietary management, and real-time data monitoring. In contrast, the control group was provided with comparable educational resources. Assessments of basic psychological needs, autonomous motivation, health behavior, and metabolic syndrome indicators were conducted at baseline and again at the 12-week mark. Results After a 12-week period, the experimental group demonstrated significant enhancements in autonomy (p = 0.004) and competence (p < 0.001), two key dimensions of basic psychological needs. Autonomous motivation (p < 0.001) and health behavior scores (p < 0.001) were also significantly higher in the experimental group, while waist circumference (p = 0.048) and systolic blood pressure (p = 0.011) were significantly reduced. Other variables such as relatedness, high-density cholesterol, fasting blood sugar, diastolic blood pressure, and neutral fat scores were also improved in the experimental group, but these changes were not statistically significant. Conclusion The autonomy support program offers a cost-effective and community-accessible health care strategy for middle-aged women and may be integrated into various nursing practices.